Ritual as Resistance in Amma Raj Joshi’s A Night’s Drama - Shah, Saroj Kumar (BMC Research Journal, 2026)
This study examines the Ratadi ritual portrayed in Amma Raj Joshi's short story A Night's Drama as a performative space through which women negotiate and challenge patriarchal authority in rural Nepal. While existing discussions of ritual in Nepali literature have largely emphasized cultural continuity and social tradition, limited attention has been given to the ways ritual performance functions as a form of symbolic resistance and gendered self-expression. Drawing on the theories of Merelman (1969), Goffman (1967), Foucault (1977), Schechner (2003), and Butler (1990), this study employs close textual analysis to investigate role reversal, performative masculinity, catharsis, suspense, peripety, and unmasking within the ritual drama. The analysis demonstrates that Ratadi temporarily inverts gender hierarchies by allowing women to enact male roles, critique domestic power structures, and collectively express experiences often silenced in everyday life. The ritual not only produces emotional release and communal solidarity but also exposes the socially constructed nature of gender identity and authority. The study concludes that Joshi's story presents ritual performance as a culturally embedded mode of resistance that simultaneously preserves tradition and creates opportunities for questioning patriarchal norms.